Influence of precursor selection on the structural integrity and electrochemical performance of ?-NaMnO2 cathode - Dogan, Ebru; Whba, Rawdah; Canbay, Canan Aksu; Arshad, Muhammad; Sahinbay, Sevda; Altin, Serdar (Wiley, 2025)
In this study, the alpha-NaMnO2 phase was successfully synthesized using three different combinations of starting materials: Na2O2/Mn2O3, Na2O2/MnO2, and Na2CO3/Mn2O3. A one-step heat treatment at 900 degrees C for 5 h under air with quenching was applied. X-ray diffraction analysis confirmed the formation of pure alpha-NaMnO2 phase in all three samples, with only slight variations in lattice parameters. Elemental and oxidation state analyses were conducted using X-ray photoelectron spectroscopy (XPS), scanning electron microscopy with energy-dispersive X-ray spectroscopy, and inductively coupled plasma measurements. XPS results revealed noticeable differences in Mn ion valence states, suggesting variations in oxygen stoichiometry and the presence of oxygen-excess structures. Electrochemical evaluations were performed in both half-cell and full-cell configurations. The samples exhibited distinct performance characteristics, with capacity fade over 100 cycles at C/3 between 1.5 and 4.3 V measured at 83.6%, 73.9%, and 83.1%, respectively. These differences correlated with the average oxidation state of Mn and O content. Full-cells, paired with presodiated commercial hard carbon anodes, showed the highest capacity for the Na2O2/MnO2 system and the best retention for the Na2CO3/Mn2O3 sample. Overall, this work demonstrates how even small variations in starting materials can significantly influence the structural and electrochemical behavior of alpha-NaMnO2.
Keywords: cathode materials; ex situ analysis; full-cell performance; hard carbon; presodiated; alpha-NaMnO2